Common fragile sites (CFS) and extremely large CFS genes are targets for human papillomavirus integrations and chromosome rearrangements in oropharyngeal squamous cell carcinoma. Issue 1 (1st November 2016) - Gao, Ge; Johnson, Sarah H; Vasmatzis, George; Pauley, Christina E; Tombers, Nicole M.; Kasperbauer, Jan L; Smith, David I.
Abstract : Common fragile sites (CFS) are chromosome regions that are prone to form gaps or breaks in response to DNA replication stress. They are often found as hotspots for sister chromatid exchanges, deletions, and amplifications in different cancers. Many of the CFS regions are found to span genes whose genomic sequence is greater than 1 Mb, some of which have been demonstrated to function as important tumor suppressors. CFS regions are also hotspots for human papillomavirus (HPV) integrations in cervical cancer. We used mate‐pair sequencing to examine HPV integration events and chromosomal structural variations in 34 oropharyngeal squamous cell carcinoma (OPSCC). We used endpoint PCR and Sanger sequencing to validate each HPV integration event and found HPV integrations preferentially occurred within CFS regions similar to what is observed in cervical cancer. We also found that many of the chromosomal alterations detected also occurred at or near the cytogenetic location of CFSs. Several large genes were also found to be recurrent targets of rearrangements, independent of HPV integrations, including CSMD1 (2.1Mb), LRP1B (1.9Mb), and LARGE1 (0.7Mb). Sanger sequencing revealed that the nucleotide sequences near to identified junction sites contained repetitive and AT‐rich sequences that were shown to have the potential to form stem‐loop DNA secondary structures that might stall DNA replication fork progression during replication stress. This could then cause increased instability in these regions which could lead to cancer development in human cells. Our findings suggest that CFSs and some specific large genes appear to play important roles in OPSCC. © 2016 Wiley Periodicals, Inc.